2015
DOI: 10.3390/nu7115483
|View full text |Cite
|
Sign up to set email alerts
|

Coleus forskohlii Extract Supplementation in Conjunction with a Hypocaloric Diet Reduces the Risk Factors of Metabolic Syndrome in Overweight and Obese Subjects: A Randomized Controlled Trial

Abstract: Limited studies have shown that Coleus forskohlii extract may aid in weight management. This randomized, double blind placebo-controlled clinical study assessed the effects of supplementation with C. forskohlii extract on key markers of obesity and metabolic parameters in overweight and obese individuals. Thirty participants completed the trial and they were randomly assigned to receive either 250 mg of C. forskohlii extract (n = 15) or a placebo twice daily for 12 weeks. All participants were advised to follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Besides, a significant decrease in appetite and increase in hunger was seen by P. vulgaris (with dose of 100 mg/day; Spadafranca et al, ), C. fimbriata (with dose of 1,000 mg/day; Kuriyan et al, ), spinach (with dose of 5,000 mg/day; Rebello et al, , Stenblom, Egecioglu, Landin‐olsson, & Erlanson‐albertsson, ), flaxseed (with dose of 2,500 mg/day; Ibrugger, Kristensen, Mikkelsen, & Astrup, ), fenugreek (with dose of 8,000 mg/day; Mathern, Raatz, Thomas, & Slavin, ), G. cambogia (with dose of 1,000 mg/day; Mayer et al, , Preuss et al, ), green coffee (Roshan, Nikpayam, Sedaghat, & Sohrab, ), and the combination simplicifolia , asiatica , Taraxacum officinale , Cynara Scolymus , Paullina Sorbilis , Alga Klamath (Rondanelli, Klersy, Iadarola, Monteferrario, & Opizzi, ), and a combination of G. cambogia and Amorphophallus konjac (Vasques et al, ; Figure ). Some other articles have shown that Gundelia tournefortii (Hajizadeh‐Sharafabad, Alizadeh, Mohammadzadeh, Alizadeh‐Salteh, & Kheirouri, ), Coleus forskohlii (Loftus et al, ), N. sativa (Mahdavi et al, ), Garcinia atroviridis (Roongpisuthipong, Kantawan, & Roongpisuthipong, ), C. fimbriata (Kuriyan et al, ), a combination of ephedra and caffeine (Hackman et al, ) as well as a combination of walnut and flaxseed (Wu et al, ) significantly reduces energy intake (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, a significant decrease in appetite and increase in hunger was seen by P. vulgaris (with dose of 100 mg/day; Spadafranca et al, ), C. fimbriata (with dose of 1,000 mg/day; Kuriyan et al, ), spinach (with dose of 5,000 mg/day; Rebello et al, , Stenblom, Egecioglu, Landin‐olsson, & Erlanson‐albertsson, ), flaxseed (with dose of 2,500 mg/day; Ibrugger, Kristensen, Mikkelsen, & Astrup, ), fenugreek (with dose of 8,000 mg/day; Mathern, Raatz, Thomas, & Slavin, ), G. cambogia (with dose of 1,000 mg/day; Mayer et al, , Preuss et al, ), green coffee (Roshan, Nikpayam, Sedaghat, & Sohrab, ), and the combination simplicifolia , asiatica , Taraxacum officinale , Cynara Scolymus , Paullina Sorbilis , Alga Klamath (Rondanelli, Klersy, Iadarola, Monteferrario, & Opizzi, ), and a combination of G. cambogia and Amorphophallus konjac (Vasques et al, ; Figure ). Some other articles have shown that Gundelia tournefortii (Hajizadeh‐Sharafabad, Alizadeh, Mohammadzadeh, Alizadeh‐Salteh, & Kheirouri, ), Coleus forskohlii (Loftus et al, ), N. sativa (Mahdavi et al, ), Garcinia atroviridis (Roongpisuthipong, Kantawan, & Roongpisuthipong, ), C. fimbriata (Kuriyan et al, ), a combination of ephedra and caffeine (Hackman et al, ) as well as a combination of walnut and flaxseed (Wu et al, ) significantly reduces energy intake (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have recognized the effectiveness of herbal plants on body fat percent (BF%), fat mass (FM), and fat‐free mass (FFM). Also, significant decrease was seen in FM and BF% by green tea (green tea with dose of 6,000 mg/day and catechins with doses of 458, 468, and 886 mg/day; Tsai et al, , Wang et al, ), I. gabonensis (with dose of 300 mg/day; Ngondi et al, ), H. sabdariffa (with dose of 75 mg/day; Chang et al, ), Phaseolus Vulgaris (with dose of 445 mg/day; Celleno et al, , Perricone, ), G. cambogia (with doses of 2,400 and 3,000 mg/day [equivalent 1,200 and 1,500 mg hydroxycitric acid]; Heymsfield et al, , Vasques et al, ), Ecklonia cava (with doses of 72 and 144 mg/day; Shin, Kim, Park, Lee, & Hwang, ), cumin (with dose of 3,000 mg/day; Zare et al, ), Coleus forskolii (with dose of 250 mg/day; Loftus, Astell, Mathai, & Su, ), Sorghum tea (with dose of 1,000 ml/day) (Yokomichi, ), Gynostemma pentaphyllum (with dose of 450 mg/day; Park et al, ), and cinnamon (with dose of 550 mg/day; Vafa et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, forskolin is one of the commercially important herbal ingredients for weight loss dietary supplements in the global market (Wagh et al, 2009;Kavitha et al, 2010;Kanne et al, 2015). Its favorable effects on body fat management have been clearly reported (Litosch et al, 1982;Haye et al, 1985;Burns et al, 1987;Shivaprasad et al, 2014) and clinical studies with oral administration of forskolin for up to 50 mg/day as a weight loss agent have not shown relevant side effects in patients (Godard et al, 2005;Henderson et al, 2005;Wagh et al, 2009Wagh et al, , 2012Kavitha et al, 2010;Sharma and Vasundhara, 2011;Hebbani Nagarajappa et al, 2015;Loftus et al, 2015).…”
Section: Forskolin As An Old Natural Occurring Camp Elevating Compounmentioning
confidence: 99%
“…) (Kanne et al, ). Notably, the natural compound forskolin has been used for centuries in traditional medicine, is considered to be affordable, and its safety has also been documented recently in modern medicine (Ammon and Müller, ; Godard et al, ; Henderson et al, ; Loftus et al, ). Forskolin directly activates the adenylate cyclase enzyme, that generates cAMP from ATP, thus raising intracellular cAMP concentrations (Seamon et al, ).…”
mentioning
confidence: 99%